Pemberdayaan Masyarakat akan Pelestarian Budaya Melayu Riau dan Pemilih Bijak dalam Pemilihan Kepala Daerah Melalui Pesta Rakyat Kampung Teluk Mesjid - Pane, Rico Purnawandi; Wardana, Muhammad Hafizhul; Anzella, Sinta; Salwa, Ega Safitri; Rahayani, Fadilah; Rezzel, Rezzel; Fitri, Salsabila Mutia; Habibullah, Masfiar; Putri, Anjelika; Pratama, Dhika Fachari Dzul; Rivanya, Aura; Fahmi, Sahrul (Abdimas Indonesian Journal, 2024)
Real work lectures (kukerta) are a form of community service activity by students. In kukerta activities, students will go directly into the community, usually in certain villages or areas, to apply the knowledge they have acquired during their studies and make a positive contribution to the local community. This year, the MBKM kukerta is being held. The MBKM kukerta is a form of effort carried out by the University of Riau in an effort to develop students' soft skills in terms of social life, organization, managing resources, managing differences, building empathy and concern for society. Riau University's real work lecture activity (Kukerta MBKM), namely the People's Festival, was held in hamlet 2, Teluk Mosque village, precisely under the bridge. Before the event was held several times before, we had made an invitation letter which we distributed to the Head of Sungai Apit Subdistrict, the head of the Teluk Mesjid Village, all the RKs and RTs of Teluk Masjid Village, and the entire community of Teluk Masjid Village. The People's Festival activities in commemoration of Youth Pledge Day succeeded in increasing the interest and talent of the people of Kampung Teluk Masjid, especially in the fields of sports and Malay arts and culture.